Sketch for a portrait of Kalkbrenner and Chopin - Jasińska, Danuta (Interdisciplinary Studies in Musicology, 2018)
In this article, the author sketches a portrait of Kalkbrenner and Chopin against the background of musical practice during the 1830s. On the basis of sources, including Chopin’s correspondence and the opinions of his contemporaries and of Chopin scholars, an attempt is made to distinguish characteristic features of the two composers in their mutual relations. Their contacts are outlined, as well as their artistic activities, with particular emphasis on Chopin’s first concert in Paris and the role of pianistic virtuosity linked with the style brillant. Attention is drawn to the properties of the Pleyel piano which Kalkbrenner and Chopin both preferred and to the differing playing aesthetics and artistic images of the two composer-virtuosos. Chosen for the purposes of stylistic comparison are their methods of piano playing, with the accent on the schematic nature of Kalkbrenner’s “finger technique”, whilst most crucial for Chopin was to bring out the beautiful quality of the sound. In the closing remarks, it is stated that the two musicians, in their pianistic, compositional and pedagogic activities, represented the distinct antithesis of one another and two different schools. Prominent in the portrait of Kalkbrenner are distinct connections with the convention of the style brillant, whilst the portrait of Chopin, who broke through those conventions, is marked by features more profound and individualised.